If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 3x + 1 = 2x + 6 Reorder the terms: 1 + 4x + 3x = 2x + 6 Combine like terms: 4x + 3x = 7x 1 + 7x = 2x + 6 Reorder the terms: 1 + 7x = 6 + 2x Solving 1 + 7x = 6 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 1 + 7x + -2x = 6 + 2x + -2x Combine like terms: 7x + -2x = 5x 1 + 5x = 6 + 2x + -2x Combine like terms: 2x + -2x = 0 1 + 5x = 6 + 0 1 + 5x = 6 Add '-1' to each side of the equation. 1 + -1 + 5x = 6 + -1 Combine like terms: 1 + -1 = 0 0 + 5x = 6 + -1 5x = 6 + -1 Combine like terms: 6 + -1 = 5 5x = 5 Divide each side by '5'. x = 1 Simplifying x = 1
| 4cos^2x-11cosx+6=0 | | 4x+14=10x+2 | | (12x-3)(x+6)= | | x+(x-9)=101 | | 4(3m+1)-2(2m+3)=3(m+4)+2+7 | | (8m+3n)(2m+5n)= | | 4x+9=10x+5 | | x^4+11x^2-900=0 | | (8m+3n)(x+6)= | | 2sec(x)tan(x)=0 | | 35-k= | | -2x^2+16x-40=0 | | 4x+11=7x+5 | | 2x+9=7x+3 | | 3/4x8x | | (4a+8x)(7a-5x)= | | -1(x-y)+3(y-x)= | | (2w+2b)(3w+5b)= | | (ln(4)^2/(2ln2)-(ln(2)^2)/(2ln2) | | 30=3x-9 | | 2lnx-6=0 | | -5=0.25(4t+20r)-8r | | 1-4x/2x-1 | | 8sinx+16=20 | | t(2+-5t+3t^2)=0 | | 8+3x=x | | n^2+4n+16=0 | | 15z-(-3x-10x)= | | 2x^2+28=1 | | 3x-5y=42 | | n^3-64=0 | | X-0.6x=12 |